2016
DOI: 10.1016/j.neuropsychologia.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Elements of person knowledge: Episodic recollection helps us to identify people but not to recognize their faces

Abstract: Faces automatically draw attention, allowing rapid assessments of personality and likely behaviour. How we respond to people is, however, highly dependent on whether we know who they are. According to face processing models person knowledge comes from an extended neural system that includes structures linked to episodic memory. Here we use scalp recorded brain signals to demonstrate the specific role of episodic memory processes during face processing. In two experiments we recorded Event-Related Potentials (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It is possible that mental time travel and autobiographical remembering, in general, is one of the motivational tools for defining how individuals perceive themselves (McAdams & Pals, 2006). Studies have indeed shown that episodic recollection helps us identify people (MacKenzie & Donaldson, 2016) and make rapid social inferences (Klein et al, 2009). According to Davidson et al (2012), episodic memory may serve as a kind of “social glue,” enabling people to form and maintain social bonds more easily.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that mental time travel and autobiographical remembering, in general, is one of the motivational tools for defining how individuals perceive themselves (McAdams & Pals, 2006). Studies have indeed shown that episodic recollection helps us identify people (MacKenzie & Donaldson, 2016) and make rapid social inferences (Klein et al, 2009). According to Davidson et al (2012), episodic memory may serve as a kind of “social glue,” enabling people to form and maintain social bonds more easily.…”
Section: Discussionmentioning
confidence: 99%